APPLICATION OF THEMATIC LEARNING IN HANDLING BASIC EDUCATION PROBLEMS AT KB-TK ARRAHMAN ISLAMIC SCHOOL - Jannati Abdullah; Siti Mayang Sari; fitria Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Basic education plays a central role in forming character, knowledge andessential skills for children. KB-TK Arrahman Islamic School, as a primarylevel educational institution, is faced with various problems that demandinnovative solutions. The application of thematic learning has emerged as apromising alternative to overcome a number of challenges in the field of basiceducation. This approach, which integrates various subjects into a particulartheme, has the potential to provide holistic solutions to various complexproblems in the world of education. The implementation of thematic learningin this school not only has an impact on students' academic aspects but also onthe development of their character and spiritual values. The aim of this researchis to describe the application of thematics in dealing with basic educationproblems at KB-TK Arrahman Islamic School. This research uses descriptivequalitative methods. Based on the facts seen at the school, researchers observedthat the implementation of thematic learning at KB-TK Arrahman IslamicSchool brought positive contributions with a holistic, contextual and relevantapproach to students' lives. The integration of subjects in themes makes it easierto understand academic concepts and overcomes the weaknesses of thetraditional model. Students are encouraged to learn actively, creatively andcritically, while adapting to a diversity of characters and learning styles. Themeselection is based on academic relevance and Islamic values. The school isresponsive to changes in learning paradigms, utilizing technology withoutsacrificing Islamic values.